KAJIAN HUKUM PERDATA TERHADAP PENGGUNAAN PERJANJIAN TIDAK TERTULIS DALAM SEWA MENYEWA RUMAH - Karman Karman (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
At this time the progress of the times is growing in addition to development, there are also high human resources, this is because several cities, regions and districts already have universities, especially in this writing in the Sambas district. With the presence of universities, both private and public, in Sambas Regency, it is very interesting for the community to gain knowledge easily without spending a lot of money (for the people of the Sambas Regency area). In this regard, many students are also outside the Sambas district to gain knowledge, therefore it is not surprising that some students rent houses and among these students make unwritten agreements or in other words only speak orally. The contract agreement is a legal umbrella with its function as protection and legal certainty for the interests of both parties. In the case of house occupancy by way of renting a house, it has also been regulated in the Republic of Indonesia Government Regulation No. 44 of 1994 concerning Occupancy of a House by Non-Owners. An unwritten agreement is an agreement that is often used in house rental transactions among students, the existence of an unwritten agreement is weaker when compared to a written agreement, especially in proving when a dispute/problem occurs. Based on this, the purpose of writing is to analyze the formation and implementation of unwritten agreements reviewed in civil law. In the discussion of the unwritten agreement, it is a valid agreement in the perspective of civil law as long as it does not conflict with government regulations contained in the civil law law. Unwritten agreements have the advantage of being efficient in the time used to reach mutual agreements and the use of trust in the formation and implementation, while the weakness is that if problems or problems occur in the future, there is no evidence on the basis of what both parties want to defend.